(untitled) (Psychology Travelogs, 2025)
Envisioning future possibilities plays a vital role in helping young individuals adapt to military realities. The way future events are mentally simulated influences decision-making effectiveness, which, in turn, impacts psychological well-being. Consequently, this research aligns with the objectives of Ukraine’s national mental health program aimed at rebuilding social capital. The concept of the future image has been explored in the works of Tytarenko, Zlobina, Lepikhov, as well as in F. Zimbardo’s time perspective theory, Tsukanova’s research, Kelly’s personal construct theory, Cherkun’s studies on temporality. However, the specific transformation of young people’s perception of the future during wartime has not been previously studied. To address the theoretical aspects of this research, we refined the definition of the "image of the future" as a cognitive construct that anticipates reality and serves as a foundation for youth’s planning and behavioral regulation. Future modeling involves retrieving and restructuring information from semantic memory (abstract knowledge, concepts, and ideas) and episodic memory (personal experiences with contextual details) to predict potential future scenarios. Based on theoretical analysis, we developed a structural model that illustrates how young individuals perceive their future, showing the connection between time perception and life prospects. The key factor in fostering an optimistic future image was reinforcing stable beliefs, positive attitudes towards upcoming opportunities, self-reflection, and trust in personal experiences. This study provided deeper insights into how young people shape their future perspectives in wartime conditions. It is a complex process that integrates past experiences, merges conceptual knowledge with personal memories, and projects them onto future possibilities. By strengthening resilient beliefs and promoting positive thinking, young individuals were able to shift towards a more hopeful outlook on the future. Further research should explore how perceptions of the future affect the socio-psychological adaptation of young people in professional settings and focus on developing and validating appropriate psychodiagnostic tools.